Husbandry risk factors associated with hock pododermatitis in UK pet rabbits (Oryctolagus cuniculus). (26th April 2014) - Mancinelli, E.; Keeble, E.; Richardson, J.; Hedley, J.
Abstract : Pododermatitis, often called 'sore hocks', is a chronic, granulomatous, ulcerative dermatitis which most commonly affects the plantar aspect of the caudal metatarsal and tarsal areas. Pododermatitis is a common clinical finding in the pet rabbit population, but no data is available regarding the actual prevalence of this condition in the UK pet rabbit population or possible husbandry‐related factors which may predispose pet rabbits to development of this condition. It was the aim of this study to determine the prevalence of pododermatitis within a sample pet rabbit population, and study possible correlations with husbandry, sex, breed and origin of the rabbits. Findings suggested that young rabbits are at a lower risk of pododermatitis compared with older rabbits; female domestic rabbits are more predisposed to pododermatitis than males; and 100 per cent of the neutered females examined showed clinical evidence of pododermatitis. The effect that different types of bedding may have on the prevalence of pododermatitis was also investigated. This study also produced a scoring system which can be used to score clinical cases. Our study is of clinical importance because it helps to recognise many of the factors which predispose pet rabbits to pododermatitis, representing the first step towards increased awareness of this extremely common problem.